2018
DOI: 10.1021/acssuschemeng.8b02151
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Assessment, Scalability, and Applications of Aerosol Lignin Micro- and Nanoparticles

Abstract: Lignin micro- and nanoparticles (LMNPs) synthesized from side-streams of pulp and paper and biorefinery operations have been proposed for the generation of new, high-value materials. As sustainable alternatives to particles of synthetic or mineral origins, LMNPs viability depends on scale-up, manufacturing cost, and applications. By using experimental data as primary source of information, along with industrial know-how, we analyze dry and spherical LMNPs obtained by our recently reported aerosol/atomization m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 70 publications
6
69
0
Order By: Relevance
“…Assis et al used the aerosol method to produce lignin macro-and nanoparticles and have reported the manufacturing costs to be in the range of 800 to 1000 €/ton based on the type of raw material used. 42 This price is quite close to the cost of producing CLPs reported in this paper at 990€/ton. A preliminary assessment for the economic potential of colloidal lignin nanoparticles is carried out by identifying the most attractive applications of CLPs from economic perspective and global market size as summarized in the Table 3.…”
Section: Economic Potential Of Colloidal Lignin Particlessupporting
confidence: 81%
“…Assis et al used the aerosol method to produce lignin macro-and nanoparticles and have reported the manufacturing costs to be in the range of 800 to 1000 €/ton based on the type of raw material used. 42 This price is quite close to the cost of producing CLPs reported in this paper at 990€/ton. A preliminary assessment for the economic potential of colloidal lignin nanoparticles is carried out by identifying the most attractive applications of CLPs from economic perspective and global market size as summarized in the Table 3.…”
Section: Economic Potential Of Colloidal Lignin Particlessupporting
confidence: 81%
“…This would make such process scalable and cost-effective, with an estimated selling price of 1015 US$ per metric ton. 41 Recently, acetone-extracted lignin from hydrothermally treated wood was converted into lignin nanoparticles via the aerosol flow reactor. The authors experimentally demonstrated the possibility of achieving lower time and temperature for particle formation.…”
Section: Dry Particlesmentioning
confidence: 99%
“…One reason for this may be their relatively higher production cost when compared to the direct utilization of lignosulfonates, or the fact that lignin particles have not yet been available in large quantities. However, recently, there has been significant advances in process engineering that is leading to large scale production of lignin particles at lower cost, 41,71 which will open opportunities for the utilization of technical lignin-based particles in large scale applications. A great advantage of lignin particles over their macromolecular counterpart is that they are readily dispersible in water, thus not being limited by solubility.…”
Section: Dispersantsmentioning
confidence: 99%
See 2 more Smart Citations